2020
DOI: 10.1186/s12862-020-01677-6
|View full text |Cite|
|
Sign up to set email alerts
|

Potential causes and consequences of rapid mitochondrial genome evolution in thermoacidophilic Galdieria (Rhodophyta)

Abstract: Background The Cyanidiophyceae is an early-diverged red algal class that thrives in extreme conditions around acidic hot springs. Although this lineage has been highlighted as a model for understanding the biology of extremophilic eukaryotes, little is known about the molecular evolution of their mitochondrial genomes (mitogenomes). Results To fill this knowledge gap, we sequenced five mitogenomes from representative clades of Cyanidiophyceae and identified two major groups, here referred to as Galdieria-typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 94 publications
4
11
0
Order By: Relevance
“…However, the G-C skew was different from the four Aspergillus species, except A. cristatum. Moreover, it showed a relatively strong preference for the C-base and that result was consistent with the study conducted by Cho et al (2020), who reported that there was a certain correlation of base skew with the geographical location and environmental pressure of the species. It was speculated that this difference was attributed to the directional mutation of the mitochondrial DNA of A. chevalieri and A. cristatum, as the dominant bacteria of dark tea fermentation, under the long-term influence of a special environment.…”
Section: Nucleotide Composition Of Mitochondrial Genomesupporting
confidence: 91%
“…However, the G-C skew was different from the four Aspergillus species, except A. cristatum. Moreover, it showed a relatively strong preference for the C-base and that result was consistent with the study conducted by Cho et al (2020), who reported that there was a certain correlation of base skew with the geographical location and environmental pressure of the species. It was speculated that this difference was attributed to the directional mutation of the mitochondrial DNA of A. chevalieri and A. cristatum, as the dominant bacteria of dark tea fermentation, under the long-term influence of a special environment.…”
Section: Nucleotide Composition Of Mitochondrial Genomesupporting
confidence: 91%
“…Mitochondrial genomes features, such as genome size, number of CDS, synteny and high CG content are shared by all the isolates and consistent with those described in previous works [69,70]. As stated by Jain et al in 2015, the high GC skew could be a consequence of the heterotrophic life of G. sulphuraria, which requires an increase of the energy request from mitochondria when it finds itself living endolithically and in the dark [69].…”
Section: General Features Of Plastid Mitochondrial and Nuclear Genomessupporting
confidence: 87%
“…For instance, the longest noncoding and most variable region in animal mitochondrial DNA is identified as Control Region (CR) and comprises a third strand of DNA, creating a D-loop [71]. In vertebrates this region has strand-specific bias and is involved in the asymmetric DNA replication mechanism [70,72].…”
Section: General Features Of Plastid Mitochondrial and Nuclear Genomesmentioning
confidence: 99%
“…Highly diverged genomic features between Galdieriales and Cyanidiales species also likely resulted in phenotypic differences (e.g., size, shape, and organelle features) and local adaptation to microhabitats 19 . Galdieriales occupies a more diverse variety of niches in extreme environments (e.g., mine drainage sites, endolithic environments) than do Cyanidiales species, whose habitats (e.g., ditches and streams near hot springs) may be more ecologically stable 13 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence (e.g., phylogeny, morphological traits, ecological habitats, and energy production systems) suggest that the Cyanidiophyceae is divided into two major orders, the Cyanidiales and Galdieriales (previously Cyanidiaceae and Galdieriaceae) 18 , 19 . Draft genome assemblies are currently available for 14 cyanidiophyceans: one strain of Cyanidioschyzon merolae , two strains of Cyanidiococcus yangmingshanensis , nine strains of Galdieria sulphuraria , and two strains of Galdieria phlegrea 9 , 14 , 15 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%